Out-of-Field Doses Produced by a Proton Scanning Beam Inside Pediatric Anthropomorphic Phantoms and Their Comparison With Different Photon Modalities - Knežević, Željka; Stolarczyk, Liliana; Ambrožová, Iva; Caballero-Pacheco, Miguel Á.; Davídková, Marie; De Saint-Hubert, Marijke; Domingo, Carles; Jeleń, Kinga; Kopeć, Renata; Krzempek, Dawid; Majer, Marija; Miljanić, Saveta; et al. (Frontiers in Oncology, 2022)
Since 2010, EURADOS Working Group 9 (Radiation Dosimetry in Radiotherapy) has been involved in the investigation of secondary and scattered radiation doses in X-ray and proton therapy, especially in the case of pediatric patients. The main goal of this paper is to analyse and compare out-of-field neutron and non-neutron organ doses inside 5- and 10-year-old pediatric anthropomorphic phantoms for the treatment of a 5 cm diameter brain tumour. Proton irradiations were carried out at the Cyclotron Centre Bronowice in IFJ PAN Krakow Poland using a pencil beam scanning technique (PBS) at a gantry with a dedicated scanning nozzle (IBA Proton Therapy System, Proteus 235). Thermoluminescent and radiophotoluminescent dosimeters were used for non-neutron dose measurements while secondary neutrons were measured with track etched detectors. Out-of-field doses measured using intensity modulated proton therapy (IMPT) were compared with previous measurements performed within a WG9 for 3 different photon radiotherapy techniques: 1. Intensity Modulated Radiation Therapy (IMRT), 2. Three-Dimensional Conformal Radiation Therapy (3D CDRT) performed on a Varian Clinac 2300 linear accelerator (LINAC) in the Centre of Oncology, Krakow, Poland, and 3. Gamma Knife Surgery performed on the Leksell Gamma Knife (GK) at the University Hospital Centre Zagreb, Croatia. Phantoms and detectors used in experiments as well as the target location, were the same for both photon and proton modalities. Total organ dose equivalent expressed as the sum of neutron and non-neutron component in IMPT were found to be significantly lower (2-3 orders of magnitude) in comparison with the different photon radiotherapy techniques for the same delivered tumour dose. For IMPT, neutron doses are lower than non-neutron doses close to the target, but become larger than non-neutron doses further away from the target. Results of WG9 studies have provided out-of-field dose levels required for an extensive set of radiotherapy techniques, including proton therapy, and involving a complete description of organ doses of pediatric patients. Such studies are needed for validating mathematical models and Monte Carlo simulation tools for out-of-field dosimetry which is essential for dedicated epidemiological studies which evaluate the risk of second cancers and other late effects for pediatric patients treated with radiotherapy.